2022
DOI: 10.1182/bloodadvances.2021004878
|View full text |Cite
|
Sign up to set email alerts
|

An IDO1-related immune gene signature predicts overall survival in acute myeloid leukemia

Abstract: The contribution of the bone marrow (BM) immune microenvironment (TME) to acute myeloid leukemia (AML) development is well-known, but its prognostic significance is still elusive. Indoleamine 2,3-dioxygenase 1 (IDO1), which is negatively regulated by the BIN1 proto-oncogene, is an interferon (IFN)-γ-inducible mediator of immune tolerance. With the aim to develop a prognostic IDO1-based immune gene signature, biological and clinical data of 732 patients with newly diagnosed, non-promyelocytic AML were retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 49 publications
1
12
0
1
Order By: Relevance
“…IDO1 activity increases T cell apoptosis, reduces T cell proliferation, and induces Tregs ( Figure 2 B) [ 140 , 141 ]. IDO1 expression in AML cells has been correlated to poor clinical outcomes [ 142 , 143 ].…”
Section: The Immune Bm Microenvironment In Chemoresistancementioning
confidence: 99%
See 1 more Smart Citation
“…IDO1 activity increases T cell apoptosis, reduces T cell proliferation, and induces Tregs ( Figure 2 B) [ 140 , 141 ]. IDO1 expression in AML cells has been correlated to poor clinical outcomes [ 142 , 143 ].…”
Section: The Immune Bm Microenvironment In Chemoresistancementioning
confidence: 99%
“…IDO1 exerts immune-regulating activity in different settings, including AML [ 194 ]. AML cells, but not normal HSCs, expressed IDO1 [ 195 ], which mediates immune tolerance [ 132 ] and correlates with a poor clinical outcome, as described above [ 142 , 143 ]. MSCs, including those isolated from myelodysplastic syndrome (MDS) and AML patients, up-regulate IDO1 following pro-inflammatory stimulation [ 86 , 193 ].…”
Section: Stromal/immune Bm Microenvironment Interplaymentioning
confidence: 99%
“…They can also produce reactive oxygen species (62) and indolamine-2, 3-dioxygenase (IDO), which both promote differentiation towards Tregs (63). Just recently, a study by Ragaini et al demonstrated that an IDO1-related immune gene signature predicts overall survival in AML (64). Another target to induce T-cell anergy is T-cell immunoglobulin and mucin domain 3 (TIM3), which binds to and is activated by galectin-9, the latter being highly expressed on AML blasts, which leads to an activation of several downstream signaling pathways such as the MAPK/ERK, PI3K-and AKT (65).…”
Section: The Role Of Lymphocytes and Monocytes In Aml Immune Escapementioning
confidence: 99%
“…In the BM of newly diagnosed AML patients, high IDO expression in MSCs was associated with elevated levels of Tregs. Furthermore, an IDO1-related immune gene signature has been identified as a negative predictor for overall survival in AML ( 99 ). Similarly, MSCs derived from Fanconi anaemia patients with AML secrete high levels of prostaglandins which resulted in Treg induction and subsequent inhibition of CD8 + CTLs ( 100 ).…”
Section: Immune Escape Of Leukemia and Lscsmentioning
confidence: 99%